Human cryptosporidiosis - Coelho, Nátalia Marinho Dourado [UNESP]; Coêlho, Juliana de Carvalho Apolinário; Inácio, Sandra Valéria [UNESP]; Coelho, Willian Marinho Dourado [UNESP]; Lima, Luiz Gustavo Ferraz [UNESP]; Corbucci, Flávio Sader [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2017)
Protozoan of Cryptosporidium genus are gastrointestinal pathogens that cause diseases of great socio-economic importance worldwide. They infect a broad range of hosts including domestic animals and humans. It continues to be a major cause of waterborne disease outbreaks and diarrhea in humans throughout the world. Is considered an opportunistic parasite, human infection predominantly results in acute self-limiting gastroenteritis, however in immunocompromised individuals or children, this disease can lead to hospitalizations and even to death. The immaturity of the immune system, low socio-economic conditions, subnutricional state or malnutrition, lack of sanitation, use of untreated water as well as inadequate hygiene habits are considered risk factors for cryptosporidiosis. Clinical findings of patients with cryptosporidiosis are similar to other diseases and if not properly identified may complicate the treatment.
Keywords: Cryptosporidiosis; Gastrointestinal disease; Human infection; Protozoan